Research on how wireless internet support student-centered learning at medical school University Malaysia Sabah (UMS) / Rosa Dewi Ismail - Ismail, Rosa Dewi (2008)
Wireless Internet technology is gaining a foothold on more and more campuses, yet few studies have investigated how wireless Internet supports and enhances a student-centered learning environment. This study seeks to fill the gap by developing an instrument to measure how wireless Internet supports student-centered learning. The purpose of the study is to investigate how the wireless internet supports student-centered learning. The advantages of the wireless internet become the independent variable in which it supports the student-centered learning. 100 questionnaires had been distributed to the first and second year students of Medical School in University Malaysia Sabah (UMS). SPSS was used to analyze the results of the study. The results found that the wireless Internet has a positive correlations and significant influence on student-centered learning by improving communication, flexibility of time and location and better personal learning style.